Is actin filament and microtubule growth reaction- or diffusion-limited? - Pausch,J; Pruessner,G (Journal of Statistical Mechanics: Theory and Experiment, 2019)
Inside cells of living organisms, actin filaments and microtubules selfassemble and dissemble dynamically by incorporating actin or tubulin from the cell plasma or releasing it into their tips’ surroundings. Such reaction-diffusion systems can show diffusion- or reaction-limited behaviour. However, neither limit explains the experimental data: while the offset of the linear relation between growth speed and bulk tubulin density contradicts the diffusion limit, the surprisingly large variance of the growth speed rejects a pure reaction limit. In this article, we accommodate both limits and use a Doi-Peliti field-theory model to estimate how diffusive transport is perturbing the chemical reactions at the filament tip. Furthermore, a crossover bulkdensity is predicted at which the limiting process changes from chemical reactions to diffusive transport. In addition, we explain and estimate larger variances of the growth speed.